THE EFFECT OF “BIOGENIC SUBSTANCES” ON THE HUMAN BODY (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article explores the impact of biogenic substances on the human body. Biogenic substances are natural compounds found in living organisms that have beneficial effects on human health. The author discusses the various ways in which these substances can positively impact the body, including boosting immunity, improving cognitive function, and reducing inflammation. Additionally, the article highlights potential sources of biogenic substances, such as certain foods and supplements, and emphasizes the importance of incorporating these substances into one's diet.